Globalization, integration and regional specialization - Christiane Krieger-Boden (Kiel Institute of World Economics (IfW), 2000)
Globalization and European integration are substantially changing the interregional division of labor in Europe and the industrial specialization of European regions, thereby potentially affecting the extent of disparities between countries and regions. This paper reviews several theoretical approaches relevant for explaining regional specialization in the process of integration (such as the new economic geography, urbanization economics, and the theory of comparative advantages), surveys the empirical evidence for European regions, and outlines an agenda for future empirical research.
Keywords: F12; F15; R12; 330; integration; regional specialization; regional income; Integration; regional specialization; regional income; Regionale Arbeitsteilung; Internationale Arbeitsteilung; Regionale Konzentration; Stadtökonomik; Komparativer Kostenvorteil; Industrie; Regionale Disparität; Theorie; EU-Staaten